A "grey" side of family business ethics?: looking into the interplay of internal and external ethical orientations : empirical insights from the wine industry - Casprini, Elena (Journal of business ethics, 2025)
Drawing on virtue ethics and stakeholder theory, the article investigates the unfolding of business ethics in the wine industry, with a focus on family businesses. Attention is specifically paid to the interplay of internal (i.e., employees-centeredness and organizational inclusiveness) and external (i.e., people-centeredness and territorial development) ethical orientations. A unique sample of 164 Italian wine businesses was built to get evidence of how the nexus of internal and external ethical orientations is handled, emphasizing the distinctive traits of family businesses. We found that employee-centeredness nurtured organizational inclusiveness and fostered people-centeredness. Interestingly, the family businesses' concern for territorial development curbed the positive implications of employee-centeredness on people-centeredness. The study results extend scholarly knowledge, shedding light on a "grey" side of family businesses' ethics.